(untitled) (Research, Society and Development, 2020)
Introduction: Educational work does not depend only on the school environment, it depends on all factors that involve the student. The project is an extension of the Pre-Hospital Urgencies and Emergencies discipline where the university extension in the community includes theoretical and practical training of elementary school children in first aid situations with the use of active methodologies in education. Objective is to report the teaching experience in guiding the use of active methodologies through the practice of the extension project where nursing students carry out health education as first aid training for elementary school children in a community in the Baixada Fluminense in the State of Rio de January. Materials and Methods: Descriptive study of the type of experience report, brings the experience under guidance of nursing students using active methodologies in health educational practice. Two strategies were used to aid in the teaching-learning process: dynamics of expository presentation and on-site practice. Discussion: The experience of applying training strategies in first aid with the use of active methodologies for children was of great relevance to the students of the project, as well as for children and teachers, as they developed good adherence and performed the practice of the content presented. Conclusion: The health education extension project in the community is considered as a methodological strategy that helps to guide children how to act in first aid situations. In this way, it contributes to knowledge with educational practices based on scientific evidence.